2001
DOI: 10.1046/j.1439-0434.2001.00688.x
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Phytoplasma Diseases in Papaya in Northern Australia

Abstract: Using molecular tools, the spread of phytoplasma diseases in a papaya plantation was investigated for 3 years to identify phytoplasma strains affecting papaya, insect vectors and alternative plant hosts. Five phytoplasma strains (SPLL‐V4, TBB, CaWB, StLL and WaLLvar) were associated with papaya yellow crinkle disease and one phytoplasma strain (PDB) was associated with papaya dieback disease. The most prevalent strains were TBB and SPLL‐V4 which occurred in 94% of infected papaya. There was a significant corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
40
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 26 publications
1
40
1
Order By: Relevance
“…This is in contrast to previous disease surveys in northern Australia, which showed that the SPLL-V4 phytoplasma is associated with diseases that occur in a wide range of plant species (Davis et al , 2003Schneider et al 1999;Padovan and Gibb 2001). The identification of a single plant species positive for the SPLL-V4 phytoplasma compared with the TBB phytoplasma (16 species) suggests that in south-east Queensland, these phytoplasmas may not have a common vector and that the vector for the SPLL-V4 phytoplasma is not prevalent.…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…This is in contrast to previous disease surveys in northern Australia, which showed that the SPLL-V4 phytoplasma is associated with diseases that occur in a wide range of plant species (Davis et al , 2003Schneider et al 1999;Padovan and Gibb 2001). The identification of a single plant species positive for the SPLL-V4 phytoplasma compared with the TBB phytoplasma (16 species) suggests that in south-east Queensland, these phytoplasmas may not have a common vector and that the vector for the SPLL-V4 phytoplasma is not prevalent.…”
Section: Discussioncontrasting
confidence: 94%
“…P. australiense, the TBB phytoplasma has a wide host range including native and introduced plant species Schneider et al 1999;Padovan and Gibb 2001;Davis et al 2003). These TBB phytoplasma-associated diseases occur throughout Australia (Davis et al , 2003Schneider et al 1999;Padovan and Gibb 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Mosaic, yellow crinkle and dieback diseases of papaya in Australia are known to be associated with phytoplasmas (Gibb et al, 1996(Gibb et al, , 1998White et al, 1998;De La Rue et al, 1999), and are the main phytosanitary problems of the Australian papaya industry, causing losses of 100 % in some plantations (Guthrie et al, 1998). Epidemiological studies in Australia have identified Orosius leafhoppers species as target candidates for transmission studies (Padovan & Gibb, 2001). In Cuba, recent reports from papaya-growing areas have confirmed that PBT is spreading (Arocha et al, 2003), but no putative insect vectors have been identified as yet.…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence that the leafhoppers, Orosius spp., are vectors of SPLL. Padovan & Gibb (2001) found SPLL-V4 phytoplasmas in the bodies of a combined sample of O. argentatus and O. lotophagorum. Based on the number and origin of specimens of O. argentatus (common brown leafhopper) in the Australian collections (APPD 2011), this leafhopper is widely distributed throughout Australia and is the vector of several phytoplasmas in Australia (Hill 1943, referred as Thamnotettix argentata, Grylls 1979, Weintraub andBeanland 2006).…”
mentioning
confidence: 90%
“…Streten and Gibb (2006) listed 28 genera of plants as hosts of the SPLL-V4 phytoplasma in Australia. In the NT, SPLL was reported on Ipomoea batatas (sweet potato) (Gibb et al 1995, Davis et al 1997, Carica papaya (papaya) , Cleoma viscosa (mustard bush), Crotalaria brevis (rattlepod), Indigofera colutea (sticky indigo), Phyllanthus maderaspanatus and Senna obtusifolia (sicklepod) ; and SPLL-V4 was reported on Aeschynomene americana (American jointvetch), Alysicarpus vaginalis (alyce clover), Arachis hypogaea (peanut), Centrosema pascuorum (cavalcade), Crotalaria goreensis (gambia pea), Medicago sativa (lucerne), Mitracarpus hirtus (tropical girdlepod), Rhynchosia minima (rhynchosia), Sesamum indicum (sesame), Vigna radiata (mung bean) (Wilson et al 2001) and C. papaya (Padovan and Gibb 2001).…”
mentioning
confidence: 99%